Lingual thyroid with severe hypothyroidism: A case report. Issue 43 (29th October 2021) - Huang, Hsuan; Lin, Yi-Hsin
Abstract: Introduction: Ectopic thyroid tissue presenting at the base of the tongue, called lingual thyroid, is a clinical rarity. Clinical presentation varies depending upon either the severity of regional symptoms associated with the enlargement of gland size, or the features related to thyroid dysfunction. Patient concerns: We reported a case of a 29-year-old female who presented with symptoms of easy fatigue and depression for 3 months. Diagnosis: After a series of diagnostic workup, the lingual thyroid with severe hypothyroidism was diagnosed. Intervention and outcome: She received conservative treatment with thyroid hormone replacement and the symptoms improved significantly. Lessons: Lingual thyroid is a rare entity that needs careful diagnostic workup including clinical examination, biochemical tests, imaging methods such as ultrasonography, scintigraphy, computed tomography, magnetic resonance imaging, and fine-needle aspiration cytology to plan the management. Lingual thyroid with hypothyroidism and no neck regional symptoms can be conservatively treated and requires regular follow-up for the prevention of potential risk of malignant transformation.